إنشاء عناقد صناعية متخصصة- تجربة العناقيد الصناعية اليابانية للسيارات- - العمودي, محمد الطاهر (جامعة الوادي - University of Eloued, 2023)
تعرف العناقيد الصناعية بإجماع معظم الإقتصاديين الدوليين على انها تجمع جغرافي لمجموعة من الشركات االتي لها علاقات تشابك مشتركة في مجال الإنتاج عمودية كانت او افقية،حيث توضح هذه الورقة النموذج الياباني للعناقيد الصناعية و الميزة الإنتاجية للشركات اليابانية، وقد أظهرت نتائج الدراسة بأن نجاح العنقود الصناعي ، يتطلب توفير مناج ملائم و خائص العنقود، حيث قامت اليابان على إثر إقرار قوانين إنشاء العنقايد الصناعية بتطوير البحث العلمي و مرونة في حركة عوامل الإنتاج،كما أن تجربة إناتج السايرات في عنقود آيتيش قد بينت مدى تأثير المناخ على العنقود و نجاحه Most international economists define industrial clusters unanimously as a geographical gathering of a group of companies that have a common intertwining relationship in the field of production, whether vertical or horizontal. This paper explains the Japanese model of industrial clusters and the productive advantage of Japanese companies. It requires the provision of an appropriate climate and the characteristics of the cluster, as Japan, following the adoption of the industrial cluster creation laws, has developed scientific research and flexibility in the movement of production factors, and the experience of sairate production in the Aytech cluster has shown the extent of the climate impact on the cluster and its success.
Estabilishingspacialed industrial cluster - the experience of industrial clusters for Japanese cars
مقال
Keywords: االيابان، عناقيد صناعية; industial cluster; industrial cars; japness economic; development research.